2020
DOI: 10.1590/1678-4685-gmb-2019-0264
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeography of the critically endangered hawksbill turtle (Eretmochelys imbricata)

Abstract: The hawksbill turtle is a broadly distributed, highly migratory and critically endangered sea turtle species. The paucity of studies restricts the comprehension of its behavior and life history. In this work, we performed a global phylogeographic analysis using a compilation of previously published mitochondrial haplotype data to understand the dynamics and diversity of hawksbill populations worldwide. Our results revealed a complex demographic pattern associated to hawksbill phylogeography since the Pliocene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
2
10
1
Order By: Relevance
“…Regarding the spatial distribution of haplotypes (H), H_1 was shared between all nesting areas, similar to the EiA01 haplotype recorded for Brazil (Vilaça et al, 2013;Arantes et al, 2020). H_10 (FN_BRA, CAR, PUR) and H_11 (FN_BRA, MEX, AUS) were shared by three areas.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Regarding the spatial distribution of haplotypes (H), H_1 was shared between all nesting areas, similar to the EiA01 haplotype recorded for Brazil (Vilaça et al, 2013;Arantes et al, 2020). H_10 (FN_BRA, CAR, PUR) and H_11 (FN_BRA, MEX, AUS) were shared by three areas.…”
Section: Resultssupporting
confidence: 70%
“…Thus, we demonstrated that the evaluated rookeries were made up of only six haplotypes, all of which were registered exclusively for these areas. Thus, these areas are genetically unique, highlighting their importance for preserving the genetic pool of the endangered species (Santos et al, 2013;Vilaça et al, 2013;Arantes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the separation between E. imbricata individuals from Indo-Pacific and Atlantic was not clearly observed in STRUCTURE using nDNA, it was slightly observed in PCA and neighborNet, and strongly detected in the MCC tree. There is a deep genetic divergence between Indo-Pacific and Atlantic mtDNA lineages of E. imbricata dating from the early Pliocene, when the closing of the Isthmus of Panama occurs (Arantes et al 2020). The geographic pattern of separation between ocean basins found with mtDNA was recovered with nuclear data, except for one individual (R0242).…”
Section: Intraspecific Studies Of C Caretta and E Imbricatamentioning
confidence: 84%
“…Other genetic studies including Brazilian sea turtles have investigated their demographic history (Bjorndal et al 2006;Vargas et al 2008;Molfetti et al 2013), population structure (Reis et al 2010a;Vilaça et al 2013;Shamblin et al 2014;Arantes et al 2020), mixed stocks at foraging aggregations (Proietti et al 2009;Reis et al 2010a;Vilaça et al 2013;Proietti et al 2014b) and interspecific hybridization (Lara-Ruiz et al 2006;Reis et al 2010b;Vilaça et al 2012;Proietti et al 2014a;Soares et al 2017Soares et al , 2018. For example, phylogeographic analyses using mtDNA showed significant genetic divergence among three Brazilian rookeries of C. caretta, suggesting the recognition of three different management units (Shamblin et al 2014), while two separate demographic units were recognized for E. imbricata in Brazilian nesting areas (Vilaça et al 2013).…”
Section: Introductionmentioning
confidence: 99%